The archetype of the Mythological Hero in News Coverage of the Covid-19 Pandemic / Архетип мифологического героя в новостных сюжетах о пандемии Covid-19 - LAVROVA ELENA N. / ЛАВРОВА Е.Н. (Наука телевидения, 2024)
The article explores the mythological model of reality construction that underlies television news programs on domestic and Western TV channels. Analyzing the main trends and contradictions in visual image functioning within the media over the past decade reveals the creation of symbolic reality as a means for people’s spiritual and practical orientation in everyday life. In today’s media culture, which is saturated with visual images, the interpretation of what is seen in the context of simulacra, recognizable visual codes, and strict construction models, becomes crucial. Deciphering the hidden meanings embedded in media materials forms the basis for understanding the cultural context of society. The Covid-19 pandemic, apart from being an informational event that affected numerous countries, also emerged as a factor influencing various economic and demographic processes. Within the media, this topic has developed into a self-contained narrative with its own plotline, characters, and actions, characteristic of a mythological cliché. It delves into matters of human life and death, thus tapping into the primordial fears and unexplored depths of the viewer’s consciousness. The analysis highlights that the media employ a mythological structure when constructing reality and providing information about the pandemic. В статье рассматривается мифологическая модель конструирования реальности, лежащая в основе телевизионных новостных программ отечественных и западных телеканалов. Анализ основных тенденций и противоречий функционирования визуальных образов в СМИ последнего десятилетия выявляет создание символической реальности как способа духовно-практической ориентации людей в повседневной действительности. В современной медиакультуре, насыщенной визуальными образами, актуализируется вопрос интерпретации увиденного в контексте симулякров, узнаваемых визуальных кодов и строгих моделей построения произведения. Расшифровка скрытых смыслов, заложенных в материалах СМИ, является основой для понимания культурного контекста общества. Пандемия новой коронавирусной инфекции Covid-19 явилась не только информационным событием, охватившим многие страны, а фактором, влияющим на многие процессы экономики, демографии. Данная тема в материалах СМИ приобрела самодостаточный сюжет со своей линией повествования, героями и действиями, свойственными мифологическому клише. Она затрагивает вопросы жизни и смерти человека, тем самым обращаясь к архаическому страху и скрытым глубинам сознания зрителя. В результате данного анализа подчеркивается: при конструировании реальности и информировании о пандемии СМИ используют модель мифологической структуры.